Evaluating perineural invasion severity in head and neck cutaneous squamous cell carcinomas to refine prognostic accuracy: A retrospective case-control study - Filippo Nozzoli; Silvia Mancini; Andrea Ambrosini-Spaltro; Emilia Crisanti; Luca Riccioni; Giovanni De Luca; Annarita Lombardi; Fabio Falcini; Rosa Vattiato; Federica Zamagni; Lorenzo Borgognoni; Serena Sestini; et al. (EJC Skin Cancer)
Aims: Perineural invasion (PNI) is a well-recognized risk factor for head and neck cutaneous squamous cell carcinoma (HNCSCC). This study investigates whether a detailed scoring system for PNI can improve prognostic accuracy in HNCSCC, beyond the traditional PNI binary assessment. Methods: Among the Emilia-Romagna Cancer Registry, we analysed 61 patients with tumour progression and 61 without, using six histological PNI features: number of nerves involved, nerve diameter and depth, intra- vs. extratumoral location, nerve sheath involvement, and presence of mitotic figures within PNI. These parameters were compiled into a cumulative PNI score, categorizing patients as high- or low-risk based on the median score. An additional 20 patients treated with immunotherapy and 25 external PNI-positive cases were included for validation. Prognostic correlations were then analyzed by Cox proportional hazards regression model. Results: Twenty-one patients (17.2 %) had PNI and 81 % of them were cases with recurrence. A significantly higher proportion of cases (81.0 %) exhibited perineural invasion compared to controls (19.0 %) (p = 0.005). High-risk PNI scores were significantly associated with worse outcomes: five-year overall survival was lower in high-risk patients (10.1 % vs. 23.3 %), and disease-specific survival was also reduced (75.0 % vs. 88.9 %). High-risk PNI scores conferred a four-fold increased risk of recurrence and nearly eight-fold higher risk of death. Among immunotherapy-treated patients, the risk of death was nineteen times higher for those in the high-risk PNI group. Conclusions: Our findings suggest that a multi-parameter PNI scoring system can refine prognostic stratification, potentially guiding more personalized treatment decisions and informing updates to the current staging guidelines.